Improved vascularization of porous scaffolds through growth factor delivery from heparinized polyethylene glycol hydrogels. (February 2017) - Janse van Rensburg, Aliza; Davies, Neil H.; Oosthuysen, Anel; Chokoza, Cindy; Zilla, Peter; Bezuidenhout, Deon
Graphical abstract: Abstract: Surface modification with heparin has previously been shown to increase vascularization of porous scaffolds. In order to determine its efficacy with sustained release, heparin (Hep) was covalently incorporated into degradable (Type D) and non-degradable (Type N) polyethylene glycol (PEG) hydrogels. After in vitro characterization of their physicochemical properties, growth factor (GF) loaded, heparinised Type D gels were formed within the pores of porous polyurethane disks, which were then implanted and evaluated in a subcutaneous model. Type N gels formed faster (3.1 ± 0.1 vs. 7.2 ± 0.2 min), were stiffer (10.0 ± 0.5 kPa vs. 7.1 ± 1.2 kPa) and more stable than degradable gels (>6 month stability vs. disintegration ⩽22 d in vitro ; all p < 0.001). Sustained release of covalently incorporated (CI) heparin from Type N (56 days; first order kinetics) and Type D (21 days; zero order kinetics) was achieved, as opposed to non-covalently incorporated (NI) heparin that eluted in a burst release within the first 2 days. While Type D gels initially impeded tissue ingrowth into the porous scaffolds, they were completely degraded and replaced by ingrown tissue after 28 days in vivo . At the latter timepoint disks containing gels without Hep or with non-covalently incorporated Hep were less vascularized than empty (no gel) controls. In contrast, the incorporation of covalently heparinized (no GF) and GF containing gels (no Hep) resulted in a 50% and 42% (p < 0.05) improvement in vascularization, while an increase of 119% (p < 0.001) was achieved with a combination of covalently attached Hep and GF. These gels thus provide a sustained release system for heparin and GF that extends the duration of their action to local tissue ingrowth. Statement of Significance: The paper describes the modification and covalent incorporation of heparin into degradable and non-degradable polyethylene glycol hydrogels in a way that provides for the hydrolytic cleavage of the linker for the release of the heparin in original and active form, and in an extended (21–56 d) controlled (zero and first order respectively) manner. The successful use of these gels as growth-factor containing and releasing matrices for the improvement of in vivo vascularization holds promise for many potential uses in tissue engineering and regenerative medicine applications, such as vascular grafts and myocardial infarction therapy, where the antithrombotic and/or growth factor binding/potentiating properties are required.